Keast Burke collection on the history of photography - Burke, Keast, 1896-1974. (1850)
Keast Burke collected examples of all types of photographic processes and equipment, and works by Australian photographers. The collection includes specimens of daguerreotype and ambrotype photography; lantern slides; albums of photographs; stereographs; negatives and glass negatives; experimental processes; portraits; landscape and pictorialist photographs; as well as cameras and other equipment.
Also includes a notebook with description of lantern slides, prints, negatives and scrapbook cuttings ; Booklet for a photographic exhibition in Denmark: Den IX Internationale udstilling af fotografisk kunst i Danmark, Charlottenborg i København, 1957 ; Booklet for photographic exhibition in Paris: XIXe salon international de photographie : du 3 au 14 octobre 1924 / organisé par la Société française de photographie et le Photo-Club de Paris.
Title from acquisitions documentation.
Burmester
Also available online
Keywords: Photography -- History; Photography -- Australia